Ultra-high resolution blood volume fMRI and BOLD fMRI in humans at 9.4 T: Capabilities and challenges - Huber, Laurentius; Tse, Desmond H.Y.; Wiggins, Christopher J.; Uludağ, Kâmil; Kashyap, Sriranga; Jangraw, David C.; Bandettini, Peter A.; Poser, Benedikt A.; Ivanov, Dimo (NeuroImage (Orlando, Fla.), 2018)
Functional mapping of cerebral blood volume (CBV) changes has the potential to reveal brain activity with high localization specificity at the level of cortical layers and columns. Non-invasive CBV imaging using Vascular Space Occupancy (VASO) at ultra-high magnetic field strengths promises high spatial specificity but poses unique challenges in human applications. As such, 9.4 T B1+ and B0 inhomogeneities limit efficient blood tagging, while the specific absorption rate (SAR) constraints limit the application of VASO-specific RF pulses. Moreover, short T2* values at 9.4 T require short readout duration, and long T1 values at 9.4 T can cause blood-inflow contaminations. In this study, we investigated the applicability of layer-dependent CBV-fMRI at 9.4 T in humans. We addressed the aforementioned challenges by combining multiple technical advancements: temporally alternating pTx B1+ shimming parameters, advanced adiabatic RF-pulses, 3D-EPI signal readout, optimized GRAPPA acquisition and reconstruction, and stability-optimized RF channel combination. We found that a combination of suitable advanced methodology alleviates the challenges and potential artifacts, and that VASO fMRI provides reliable measures of CBV change across cortical layers in humans at 9.4 T. The localization specificity of CBV-fMRI, combined with the high sensitivity of 9.4 T, makes this method an important tool for future studies investigating cortical micro-circuitry in humans. [Display omitted] •CBV-sensitive VASO was implemented at 9.4 T for layer-dependent fMRI in humans.•9.4 T VASO is challenging due to: blood-inflow, SAR, T2*-decay, B1+and B0 constraints.•Alternating pTx shimming and advanced adiabatic pulses can overcome these challenges.•Layer-dependent CBV changes can be reliably detected in human motor cortex at 9.4 T.